Acoustics of Portuguese Romanesque churches - António P. O. Carvalho (2019)
This paper summarizes the results of recent measurements in ten very typical Romanesque churches in the North of Portugal to acoustically characterize this type of building. In situ measurements were done regarding Reverberation Time (RT) and Rapid Speech Transmission Index (RASTI) in empty churches. The results are presented and compared with seven architectural characteristics of the churches (area, volume, ceiling height, length, width, etc.). Statistical correlations and prediction equations are presented among those seven architectural parameters and the two acoustic parameters measured (RT and RASTI). Values up to 0.91 were found for the related R2 coefficients.